Pengaruh Likuiditas, Leverage, Profitabilitas, Dan Sales Growth Terhadap Financial Distress - Cheristin Natalia, Thio Lie Sha (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to examine the effect of liquidity, leverage, profitability and sales growth towards financial distress on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. This study using 36 companies that have been selected through a purposive sampling method. Data processing techniques using multiple regression analysis what helped by Eviews (Econometrical Views) program version 10 and Microsoft Excel 2016. The results show that leverage and profitability have positive significant effect on financial distress, while liquidity and sales growth has no significant effect on financial distress. The implication of this research is the need of policy to buy some assets in order to maintain the level of debt of the company, so it will minimizing the occurrence of financial distress.